Acerca del perfil agentivo de las pasivas - Delbecque, Nicole (Studia Romanica Posnaniensia, 2004)
The modulation of the relationship between the "downstream" subject of passive constructions and the upstream participant, expressed by an oblique, is a function of the parameters continuity/discontinuity and substantiality/circumstantiality. The preposition used is revealing how the two axes combine. Por 'by' differs from de 'of, con 'with' and en 'in', in that it yields a discontinuous yet substantial view of the relational profile. The discourse orientation of the agent's "conditioning" intervention does not only vary according to the kind of passive construction and the kind of entity denoted by the oblique, but also crucially hinges on the semantic category of the verb.